Development and Characterization of FLT3-Specific Curcumin-Loaded Polymeric Micelles as a Drug Delivery System for Treating FLT3-Overexpressing Leukemic Cells - Singkome Tima (2018)
© 2016 American Pharmacists Association® This study aimed at developing a curcumin (CM) nanoparticle targeted to Feline McDonough Sarcoma (FMS)-like tyrosine kinase 3 (FLT3) protein on the surface of leukemic cells and at evaluating their properties, specificity, cytotoxicity, and inhibitory effect on FLT3 protein level in FLT3-overexpressing leukemic cells, EoL-1, and MV-4-11 cells. FLT3-specific peptides were conjugated onto modified poloxamer 407 using the copper-catalyzed azide-alkyne cycloaddition reaction. The thin film hydration method was performed for FLT3-specific CM-loaded polymeric micelles (FLT3-CM-micelles) preparation. Flow cytometry and fluorescence microscopy were used to determine rate of cellular uptake. 3-(4,5-dimethythiazol-2-yl)-2,5-diphenyl tetrazolium bromide assay was used to test the cytotoxicity of the micelles on leukemic cells. FLT3-CM-micelles demonstrated a mean particle size less than 50 nm, high entrapment efficiency, and high rate of CM uptake by leukemic cells. The intracellular CM fluorescence is related to FLT3 protein levels on the leukemic cell surfaces. Moreover, FLT3-CM-micelles demonstrated an excellent cytotoxic effect and decreased FLT3 protein expression in the leukemic cells. The FLT3-CM-micelles could enhance both solubility and cytotoxicity of CM on FLT3-overexpressing leukemic cells. These promising nanoparticles may be used for enhancing antileukemic activity of CM and developed as a targeted drug delivery system in the future.